Investment Promotion for Community Economic Development of Special Economic Zone: Study of Sez Mandalika and Bitung in Indonesia - Rustidja, Ery Supriyadi; Purnamawati, Ami; Setiawati, Rosati (European Journal of Economics and Business Studies, 2017)
Image is not merely a visual impression but a comprehensively perceived impression of something. This study focuses on image of zone defined as information association of location, important element signature of a cultural civilization, and visuality of region including Special Economic Zone (SEZ). The Clear, well- organized and presented information of Social-cultural potency, economic growth, environment, and accessibility of a region determines the positive image of zone. A comprehensive visual impression of SEZ does not only accelerate the inflow of investments into the SEZ but also grows economic activity. Bitung and Mandalika as two Special Economy Zones in Indonesia have different characteristics. Bitung is a manufacturing of agriculture and ocean based region while Mandalika is a tourism based one. The efforts of developing positive image of zone have main position for investments as they encourage the realization of growth centers and service centers, connect and function the intraregional and interregional activities. Using the participative obstructive, this qualitative study finds that imaging of SEZ recognizes the region strategic value from the interests of social-cultural, social-economic, efficient usage of natural resources, usage of technology, the environmental function and capability. Through investment promotion, the image of zone is concerning the products and service fulfilling the expectations of investors and the users; therefore in long term this could provide multiplier effects, benefits, value added as well as the achievement of performance target of SEZ as strategic area. Investment promotion in both zones has more orientation toward linkage and acceleration values for SEZ realization for both investors and zone potency. The other findings of the study show that Mandalika SEZ emphasizing on promotion of competitiveness strategy, value chain, and tourism network, in another hand Bitung SEZ focusing more on promotion strategies for increasing value-added logistics, profit, benefit, and supply chain of industry. The investment promotion of SEZ has implications for policy of attracting financial investment to SEZ, organizing zone, and controlling spatial structure and pattern of SEZ in accordance with regional spatial plan.